Studies in Tractate Eruvin of the Talmud Bavli : structure, language, redaction, and halakha - Zur, Uri (Academic Studies Press, 2020)
"This volume collects several articles by scholar Uri Zur on various areas in the field of Jewish studies. Topics discussed include different types of structure in Talmudic texts from a literary point of view, the study of the Aramaic language utilized in the Bible and the Talmud from a linguistic and interpretive perspective, the redaction of sugyot in the Talmud Bavli analyzed from a textual point of view, and matters of halakha and halakhic rules. The author also examines contemporary topics such as modern Judaism in Israel and peacemaking efforts grounded in the Pentateuch and Jewish tradition"--